Performance of Perkasa Pangasiid (Pangasianodon hypophthalmus) from family selection results - Evi Tahapari; Jadmiko Darmawan; Suharyanto suharyanto (IJOTA (Indonesian Journal of Tropical Aquatic), 2020)
Perkasa pangasiid (Pangasianodon hypophthalmus) is a superior catfish selected by the family that has been released by the Minister of Marine and Fisheries as aquaculture fish which has a selection response of 38.86 %. Genetic quality improvement to accelerate growth can be done through selection activities. The performance test of the Siamese catfish from the selection (Perkasa strain) compared to the non-selection strain (local strain) originating from the farmer. The purpose of this study was to compare the productivity of selection and non-selection Siamese catfish cultivation maintained in a net pond. The initial seeds of the test fish were 3.76 g to 3.79 g with a total length of 2 inches to 3 inches kept in a net pond measuring 3 × 5 × 1.25 m. The water level was around 100 cm with a density of 175 fish/net. Maintenance was carried out for six months. Test parameters observed included: weight gain, specific growth rate, biomass harvest, productivity and cost of production. The results showed that Siamese catfish which were selected for six months of maintenance had a final weight of 698.40 ± 164.54 g and non-selection strains of 595.77 ± 103.41 g. As well as having a higher specific growth rate (3.51 %), higher harvest biomass (11.44 %), and higher productivity (18.71 %) than non-selection Siamese catfish. Based on the bioeconomic analysis, the selection of enlarged Siamese catfish cultivation can reduce production costs up to Rp 390 /kg. The use of Perkasa Pangasiid superior seeds can increase harvest biomass higher than the non-selection seeds.